Dialogic Feedback on Graduate Students' Thesis Writing Supervision: Voices of Indonesian Graduate Students - Sarai Enita; Sumardi Sumardi (AL-ISHLAH: Jurnal Pendidikan, 2023)
Researchers have become increasingly interested in the notion of dialogic feedback in higher education. Despite its growing awareness of dialogic feedback, relatively little is known about how dialogic feedback is perceived through the lens of graduate students in the thesis supervision context. Hence, the purpose of this study is to explore the perceptions of graduate students regarding dialogic feedback during thesis proposal writing in a group supervision setting. An Interpretative Phenomenological Analysis (IPA) was undertaken to investigate the feedback experiences. Five TESOL graduate students were recruited to participate in semi-structured interviews and observations regarding supervision meetings. Two themes emerged from the findings. The first is the role of dialogic feedback in preventing students’ misunderstanding and cultivating students’ reflective thinking. Findings indicated that dialogic feedback could help improve students’ writing skills and thesis progress. The second is the positive and negative emotions encountered in the dialogic feedback experience. It contains feelings of low self-confidence, no fear of negative correction, and feelings of being motivated. The implication of the study brought to light the impact dialogic feedback has on thesis progress as well as providing a view of the dynamics between students' and supervisors' interactions in dialogic feedback experience.